Learning digital skills online: empowering older adults through one-to-one, online digital training provision - Wilson-Menzfeld, Gemma; Gates, Jessica Raven; Moreland, Mary; Raw, Helen; Johnson, Amy (Frontiers in Psychology, 2023)
Introduction Digital exclusion, through lack of access and poor digital skills, can have an adverse impact on daily living. Not only did the COVID-19 pandemic dramatically impact the necessity of technology in our daily lives, but also reduced the availability of digital skills programmes. This study aimed to explore perceived facilitators and barriers of a digital skills programme that was delivered remotely (online) and to reflect on this form of training as a possible alternative to traditional face-to-face models. Methods Individual interviews were carried out with programme participants and the programme instructor. Results Two themes were generated from this data: (a) Creating a unique learning environment; and (b) Encouraging further learning. Discussion Barriers to digital delivery were evident, however, the individual and personalized delivery empowered participants within their own learning, supporting individuals to learn skills relevant to them and to continue their digital learning journey.